2004
DOI: 10.2337/diabetes.53.3.775
|View full text |Cite
|
Sign up to set email alerts
|

Potential Contributory Role of H-Ras, a Small G-Protein, in the Development of Retinopathy in Diabetic Rats

Abstract: Hyperglycemia is thought to be the underlying factor in the development of diabetic retinopathy, but the mechanisms involved remain partially understood. Diabetes increases oxidative stress, and reactive oxygen species affect the interactions between a small-molecularweight G-protein, H-Ras, and several of its effector proteins. The purpose of this study was to examine the regulatory role of H-Ras in glucose-induced apoptosis of retinal endothelial cells. The expressions of H-Ras and its effector protein (Raf-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 46 publications
(57 reference statements)
1
61
0
Order By: Relevance
“…Accelerated apoptosis of endothelial cells can result in capillary closure because the increased turnover can prematurely exhaust the cell's replicative capability and because pericytes probably do not replicate in the adults (25), their accelerated death is likely to result in pericyte ghosts. Histopathology of diabetic retinopathy takes over a year to develop in rats (17,26), but apoptosis is a rapidly consummated phenomenon, and the cell contains fragmented DNA for only a few hours (27). Thus, a small number of TUNEL-positive cells observed in diabetic retina (8,9) along with defective endothelial replication may well be sufficient to account for the pericyte loss and formation of acellular capillaries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accelerated apoptosis of endothelial cells can result in capillary closure because the increased turnover can prematurely exhaust the cell's replicative capability and because pericytes probably do not replicate in the adults (25), their accelerated death is likely to result in pericyte ghosts. Histopathology of diabetic retinopathy takes over a year to develop in rats (17,26), but apoptosis is a rapidly consummated phenomenon, and the cell contains fragmented DNA for only a few hours (27). Thus, a small number of TUNEL-positive cells observed in diabetic retina (8,9) along with defective endothelial replication may well be sufficient to account for the pericyte loss and formation of acellular capillaries.…”
Section: Discussionmentioning
confidence: 99%
“…The rats were weighed two times a week, and their food consumption was measured once every week to calculate the amount of ␣-lipoic acid consumed. GHb was measured at 2 months of diabetes, and every 3 months thereafter, using affinity columns (kit 442-B; Sigma Chemicals) (17). At the end of the experiment (11 months' duration), the rats were killed by overdose of pentobarbital, and the eyes were removed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PI3K/Akt and ERK1/2 pathways have been shown to regulate MMP-2 and -9 expressions in diabetes including diabetic retina [56,57]. Diabetes activates a small molecular weight G-protein, H-Ras, in the retina, and its capillary cells is implicated in the apoptosis of retinal capillary cells [54,57]. It was shown that H-ras regulate MMP-9 induction; hence, its activation is associated with increased vascular permeability in diabetes.…”
Section: Mmps and Cell Signalingmentioning
confidence: 99%
“…Results of a recent research suggest that the pathways activated by Ras and many of its intermediates play a crucial role in the diabetes-associated complications including retinopathy [23,[49][50][51]. Glucose-induced biochemical alterations induce ROS, often activate Raf-1-MAPK/ERK kinase (MEK)-ERK cascade via Ras, and activate a cascade of signaling pathways leading to cellular dysfunction or death [52][53][54][55]. The PI3K/Akt and ERK1/2 pathways have been shown to regulate MMP-2 and -9 expressions in diabetes including diabetic retina [56,57].…”
Section: Mmps and Cell Signalingmentioning
confidence: 99%